Physiological responses of oil palm (Elaeis guineensis Jacq.) seedlings under different water soil conditions (2016)
Water supply is the main yield-limiting factor of oil palm crops. A water deficit affects virtually all aspects of metabolism and plant structure, while a water excess leads to waterlogging, an abiotic stress that affects crop production because of a reduction of oxygen in the soil. To determine the effect of water stress on the physiology of oil palms (Elaeis guineensis) during the nursery stage, clones from three embryogenic lines of three different ortets (LE 33-7, LE 28-59 and LE 16-79) were subjected to four water conditions (moderate deficit, field capacity, partial and continuous waterlogging) for 60 days under a completely randomized split-plot design with four replications. The gas exchange, vegetative growth and nutrient content variables were evaluated. There was no interaction between the water conditions and embryogenic lines for any variable. The moderate water-deficit stress significantly reduced the stomatic conductance, photosynthesis, transpiration and growth. Under waterlogged conditions, the seedlings developed root aerenchyma and pneumatophores as adaptation mechanisms, and their gas exchange or their micronutrient reduction and assimilation processes (with the exception of copper) were not affected. However, under permanent waterlogging, the seedlings had poor growth because of higher leaf respiration rates and probably pneumatophore maintenance and imitations in the absorption and transport of macronutrients. while the plants under partial waterlogging exhibited a growth pattern similar to that observed under optimal soil moisture conditions.